A smart safety cane for human fall detection. (2015) - Chen, Ping-Hsu; Li, Yung-Hui; Chiou, Che Wun; Lee, Chiou-Yng; Lin, Jim-Min
Lots of countries have gradually become an aging society, therefore, the safety issues of the elderly attract more and more attentions. Falling is one of the major reasons for the accidental injuries of the elderly, and many times such accidents have become irreparable regrets because of the delayed arrival of the ambulances. In this study, we propose to attach to the cane with intelligent embedded system with acceleration detection ability. Such system is able to collect the 3D acceleration data of the cane when it is used by the elderly in real time. We analyse the data with finite state machine in order to detect the fall accidents of the elderly. The smart cane is able to send alarm and location of the elderly to the hospital as soon as such accidents are detected, so that the ambulance can be dispatched immediately after the accident happened.